DURABILITY STUDY OF CONCRETE WITH ELECTRONIC WASTE PLASTIC AGGREGATE (Advances in Civil and Architectural Engineering, 2021)
This study aims to determine the durability of concrete, in which plastic chips originating from the casing and enclosures of small electronic items are used as a part of coarse natural aggregate. The following three amounts were used: 50%, 70%, and 90% of the aggregate by volume. The concretes were tested after 28 days of standard curing as well as after exposure to physical (25 freeze-thaw cycles and 25 wet-dry cycles) and chemical (HCl, MgSO4, and NaOH) aggressive influences. Durability was evaluated based on changes in both flexural and compressive strength after exposure. The results of the corrosion resistance tests confirm the different types of behavior of the samples, depending on the relative proportion of the plastic aggregate. In terms of a comprehensive evaluation of the experiment, the greatest potential was found in concrete with 50% plastic chips, which can be defined as lightweight-low strength concrete. However, the specific compressive strength (strength to density ratio) increased with increasing amounts of plastic aggregate, which is a good standpoint for recycling this waste if specific applications are identified that can accept the technical limits of this material while using the positive parameters that could be useful for the application.